An Empirical Investigation to Explore the Glass Ceilings Faced by Women Managers of Maldives Using Thematic Analysis - Aroosha, Aminath (2010)
This research explores the glass ceilings faced by women managers of Maldives. The study revealed that glass ceilings or ‘invisible barriers’ exist in Maldivian work environment that hinders women from achieving senior positions. Taking the narratological approach, this research interprets the experiences of seven female managers of Maldives, and being member of the tribe, my personal experiences are shared when the stories of these women were interpreted using thematic analysis. The findings of this research revealed that Maldivian women managers have been prone to various glass ceilings that have been directly related to their job and indirectly related to their job. Hence, the data exposed direct barriers such as perception of male employees towards the female employees, harassment and bullying at work and also various forms of discrimination which led to frustration of the managers. Indirect barriers appeared as the dual role of working women acting as an indirect barrier along with the need for family support and the lack of support facilities for working women act as indirect glass ceilings which they face outside their jobs.